Teori Nasikh-Mansukh dalam Alquran (Pendekatan Tafsir Maudhu’i) - Rupi’i Amri (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
Nasikh-mansukh in the Qur’an is an interesting theme to be studied as always. This is due to the Qur’an, on the one hand as the holy book of Muslims which does not contain contradictions (ikhtilaf), as ex- plained by the Qur’an (Qs An-Nisa ‘/ 4: 82), but, on the other hand, the Qur’an, in some verses, mentions the word nasakh, as in Qs Al-Baqar- ah / 2: 106. The scholars, in this concern, differ in explaining the word nasakh in the verse. Differences of opinion on this issue are broadly grouped into two. First, a group that support the existence of nasakh in the sense of abrogation in the Qur’an. The scholars who support this view are Ibn Kasir and Ahmad Mustafa al-Maragi. Secondly, a group that reject the existence of nasakh in the sense of abrogation. This group prefers to mention the word nasakh with takhsis (specializing). This is done to avoid the understanding of the cancellation of the Qur’anic law revealed by Allah. The scholars included in this group are Abu Muslim al-Asfahani, ‘Abd al-Muta’al al-Jabri, and Muhammad al-Bahi.